The phenomenon of infection with abdominal wall reconstruction. - Engelsman, A; van der Mei, H; Ploeg, R; Busscher, H (2007)
This review presents the clinical background to abdominal wall reconstruction, the different types of surgical meshes employed and known mechanisms of infection. It is shown that there are major physico-chemical differences between available meshes, which, in combination with the location of the mesh, the surgical technique applied and hernia type involved influence the infection potential.